Pengembangan Bahan Ajar Menulis Teks Cerpen Berdasarkan Teknik Storyboard pada Siswa Kelas XI SMA - Ika Novita; M. Siddik; Asnan Hefni (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
The purpose of this study was to develop teaching materials for writing short stories based on storyboarding techniques in class XI high school students, to know the feasibility of teaching materials for writing short stories based on storyboarding techniques in class XI high school students and to know the effectiveness of short story writing teaching materials based on storyboard techniques in class XI High school. This research is a research development or Research & Development (R&D). Research and Development is a research method used to produce certain products and test the effectiveness of products in the form of teaching materials to write short stories based on storyboarding techniques for class XI high school students. This development research resulted in the feasibility of the product being developed, a validation test involving media expert lecturers with an average score of 4.5 and Indonesian language professors with an average score of 4.66 and trials on students with an average score of 4, 45 with very good criteria. The eligibility criteria for teaching materials developed with a percentage of eligibility of 89%, the teaching material for writing short stories based on storyboarding techniques for class XI high school students is very feasible to use. To achieve the objectives of teaching and learning activities must be done efficiently in its implementation to be effective and efficient. The feasibility assessment of this module includes four aspects namely, the content / material aspect, the presentation aspect, the language aspect and the graphic aspect.